Pengukuran Tingkat Kematangan Tata Kelola Teknologi Informasi Berdasarkan Framework COBIT 4.1 Proses Acquire and Implement (AI) pada PT. Samudra Sarana Logistik - Rusdy Hasan Puspitoputra; Yusi Tyroni Mursityo; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
An assessment of the maturity level of IT governance in the application of information technology using the COBIT 4.1 framework specifically domain Acquire and Implementation case studies at PT. Samudra Sarana Logistik. COBIT (Control Objective for Information and Related Technology) Version 4.1 is one of the most widely used IT Governance standard frameworks. This research is focused on one main COBIT domain, namely Acquire and Implementation (AI) at PT. Samudra Sarana Logistik, the research method consists of observation, interviews and data analysis using the COBIT Version 4.1 framework. The results of the evaluation of the measurement of the Maturity level of AI 1 is at level 2 (Repeatable but Intuitive), Maturity level of AI 2 is at level 2 (Repeatable but Intuitive), Maturity level of AI ​3 is at level 2 (Repeatable but Intuitive), Maturity level of AI 4 is at the level 5 (Optimized), Maturity level of AI 5 is at level 3 (Defined), Maturity level of AI 6 is at level 1 (Initial / Ad Hoc), and the maturity level of AI 7 is at level 2 (Repeatable but Intuitive). From differences that arise in the gap analysis, the results of the gap analysis can be make 11 recommendations which will help the company in increasing the level of maturity to be achieved.